Enhanced New Product Development Framework: A Novel Approach for Developing Successful Products - Hussain, Shafaat (Digital Repository of Theses - SSBM Geneva, 2024)
The success rate of new product launches in the United States market is very low, with an estimated failure rate of around 95% out of nearly 30,000 debuts per year. This pattern of failure affects not only newly founded enterprises but also well-established market leaders. This research primarily aims to analyze the fundamental processes involved in attaining success in new product development, with a focus on identifying key components that significantly contribute to high success rates in newly introduced products. The goal is to create a New Product Development Framework that may increase the likelihood of successful product launches, thereby having a substantial impact on the field of new product development. The research employed industry surveys and interviews to understand the dynamics of product development frameworks and identify issues within them. Based on descriptive analysis of the survey results and content analysis of the interview transcripts, the “Enhanced New Product Development Framework” was conceptualized. This framework was subsequently tested in a 12-month case study, ultimately achieving $24K in recurring revenue with the newly developed product.